ASAS GRADUALITAS HUKUM ISLAM DAN APLIKASINYA DALAM LEGISLASI HUKUM ISLAM DI INDONESIA (1974-2011) - Jeje Jaenudin (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2020)
From 1974 until 2011, as many as 14 legislations covering 8 areas of the Islamic law has been enacted in Indonesia. The establishment of Islamic law taken based on the foundation and basic principles as when it is prescribed Allah to His Messenger. Such principles “ ’Adam al Haraj” , “Taqlîl al Takâlif ”, “Musâyarat bi al Maslahat”  , and "Al Tadarruj". The fact legal developments in Indonesia shows that the principle of tadarruj been practiced in the process of establishing Islamic law. Both in order to strengthen the existence and position, and in an effort to expand the fields of Islamic law legislated in the frame of national legal systems. But have not found a standard formula became oprational guidelines in the application of tadarruj principle on  Islamic legislation in Indonesian legislation system. This study analyzes how the principle of graduality (tadarruj) formulated and applied to the tasyri’, and taqnîn. Then look for a applicated formulation of the principle of tadarruj on Islamic legislation in Indonesian law system frame. This study is a normative legal research with descriptive analytical method. The approach taken is the approach of laws ( statue approach) and the history of laws (historical approach). The focus of research is examining the legal doctrine that tadarruj principle and its application. The theories used in this study are the state of law theory, the legal systems theory, and the legislation with principle of tadarruj theory. The findings of this study : The application formulation of tadarruj on Indonesian Islamic legislation is the establishment of Islamic laws gradualy and slowly through steps: (1) laying philosophical and juridical foundation on the state philoshopy and constitution; (2) entering an Islamic law material to a national legislation and regulation; (3) establishment of an independent Islamic law; (4) implementation, evaluation, and revision of Islamic legislation from time to time in accordance with the social changes and development of civilization and culture.